2020
DOI: 10.1111/jfb.14450
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of circumtropical almaco jack, Seriola rivoliana: tool for conservation and management

Abstract: The almaco jack, Seriola rivoliana, is a circumtropical pelagic fish of importance both in commercial fisheries and in aquaculture. To understand levels of genetic diversity within and among populations in the wild, population genetic structure and the relative magnitude of migration were assessed using mtDNA sequence data and single nucleotide polymorphisms (SNPs) from individuals sampled from locations in the Pacific and Atlantic Oceans. A total of 25 variable sites of cytochrome c oxidase subunit 1 and 3678… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
0
7
1
Order By: Relevance
“…In this study, the results of adaptive genomic differentiation between the sampled patches of S. rivoliana showed higher values of F ST than those previously reported based solely on neutral markers (Mendoza‐Portillo et al, 2020). There are still several uncertainties around the detection of loci that are under selection that may influence disparate patterns between neutral and outlier loci.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In this study, the results of adaptive genomic differentiation between the sampled patches of S. rivoliana showed higher values of F ST than those previously reported based solely on neutral markers (Mendoza‐Portillo et al, 2020). There are still several uncertainties around the detection of loci that are under selection that may influence disparate patterns between neutral and outlier loci.…”
Section: Discussioncontrasting
confidence: 61%
“…It is therefore essential to define population units for their adequate future management, particularly where resources are shared between countries. Unfortunately, little is known about the broader genomic structure and diversity of S. rivoliana , but using a suite of neutral single‐nucleotide polymorphisms (SNPs), Mendoza‐Portillo et al (2020) identified three populations in the Pacific Ocean and found high levels of gene flow between them. These populations did not follow a pattern of isolation by distance, suggesting that environmental variability may be a driver of population divergence and could be responsible for genomic structuring.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern has been recovered in populations of the blue-banded goby ( Lythrypnus gilberti ) distributed in the Galapagos Islands, where the oceanographic conditions have promoted an adaptive process ( Bernardi, 2022 ). Although the growing evidence that the use of markers generated by NGS help us characterize the genetic structure of marine species, there are still very few examples of studies using NGS in the TEP ( Mendoza-Portillo et al, 2020 ; Bernardi, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, adaptive potential is becoming increasingly important due to the rapidly appearing effects of human-induced climate uncertainty in addition to stochastic fluctuations of the environment 4 , 5 . Therefore, analysing levels of genetic diversity is considered to be integral in deciding which populations should be prioritised for protective action 2 , 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%